Intramedullary spinal cord abscess associated with right-to-left shunt via right superior vena cava draining into left atrium: A case report. Issue 26 (30th June 2022) - Hirose, Satoshi; Sudo, Naohiro; Okada, Masahiro; Natori, Naotoshi; Akimoto, Takayoshi; Hara, Makoto; Nakajima, Hideto
Abstract : Rationale: Intramedullary spinal cord abscess (ISCA) is a rare but treatable bacterial infection of the central nervous system, and the etiology in no less than 40% of the cases is cryptogenic. Although a few cases of ISCA in individuals with a right-to-left shunt (RL shunt) have been reported, only few arguments focused on the association between RL shunt and ISCA have been provoked. The right superior vena cava (RSVC) draining into the left atrium (LA) is an uncommon systemic venous anomaly that results in an RL shunt, and this anomaly causes several types of neurological complication such as stroke or brain abscess. We report the first case of ISCA associated with RSVC-LA RL shunt. Patient concerns: A 36-year-old man developed progressive paraparesis, dysuria, and spontaneous pain in the lumbar region and lower extremities. Spinal magnetic resonance imaging revealed an intramedullary lesion extended from Th12 to L2 with ring-shaped gadolinium enhancement. Cerebrospinal fluid (CSF) study exhibited a marked pleocytosis, and CSF culture grew Streptococcus intermedius . Cardiovascular computed tomography angiography identified RSVC-LA RL shunt, which caused transient acute cardiac syndrome due to air embolus. Diagnoses: The patient was diagnosed with ISCA associated with an RSVC-LA RL shunt. Interventions: The patient was treated with a combination of intravenous administration of meropenem and vancomycin in a daily dose of 6 and 2.5 g, respectively, followed by intravenous administration of ampicillin in a daily dose of 750 mg. The intravenous antibiotic therapy was continued for 37 days. Outcomes: A favorable neurological outcome was obtained by the intravenous antibiotic therapy, and recurrence of infection was prevented by continuous oral antibiotic therapy for 18 months. Lessons: With a literature review of ISCA associated with RL shunt, we insist that screening for RSVC-LA is beneficial to patients who are diagnosed with cryptogenic ISCA as its identification leads to appropriate preventive therapy.